Mapping the global Islamic equity market vis-à-vis the COVID-19 turbulence - Rizaldy, Muhamad Rizky; Rahayu, Siti (Jurnal Ekonomi & Keuangan Islam, 2021)
Purpose – COVID-19 typically affects economic activity and growth, including the movement of global Islamic stock indices. This experimental study intends to analyse and map the global Islamic equity markets competition and identify which countries have the best performance while facing the turbulence of COVID-19. Methodology – This research was conducted by simulating the formation of a global Islamic stock portfolio and ranking based on weighting of investment allocations in each country. The data used were monthly data during the first year of the COVID-19 crisis period from 12 countries that provide an Islamic stock index and are constituents of Dow Jones Global Islamic Indices and/or FTSE Shariah. The Single Index Model was employed as the method in the formation of the global portfolio in this research. Findings – Our analysis revealed that four countries that deserve the biggest weights, namely China, Japan, Turkey, and Malaysia, were the countries with the best relative performance compared to their risk and the most defensive countries to the global systematic market risk and turbulence during the first year of COVID-19 crisis period. On the other hand, three countries were eliminated as their Excess Return to Beta were lower than the Cut-Off Point, these countries were the United Kingdom, United Arab Emirates, and Canada, which means that the returns of these countries were not worth the risks. Originality – While some studies have analysed the behaviour of Islamic stock markets during the COVID-19 crisis, none of them tried to map the global Islamic stock market that reflects the competitiveness of the constituent countries and the competition amongst them. Practical implication – This research argues that if Islamic multinational investors allocate their funds while facing the COVID-19 turbulence by considering the global map generated from this study, the investors will have a global Islamic investment portfolio with an optimal return which is higher than the market return and minimal risk which is lower than the market risk.